KEARIFAN LOKAL PERMAINAN TRADISIONAL UCING BANCAKAN UNTUK MENGEMBANGKAN KEMAMPUAN MOTORIK SISWA KELAS iv - Desi Rahmawati; Anggraeni, Relita; Alfiatunnimah, Vivi; Tarmidzi; Khodari, Rahmad (STKIP Muhammadiyah Kuningan, 2024)
Traditional games are a cultural heritage that has been played downward and downward for hundreds of years. This game, according to some investigations, is capable of developing students' physical motor skills. However, today, traditional games are beginning to be abandoned by children because they are more interested in playing with exercise. Seeing the many benefits that can be taken from this traditional game, then this game is very worthy to be introduced back to the students through the method of learning at school. Punching is one of the traditional games that is rarely played by children, although researchers are convinced that it can improve the morotic physique of elementary school students. To that end, the researchers conducted research aimed at developing the motor skills of students through the traditional methods of Bancakan. Although a lot of research has been done on this tradition, there is still a gap that has not been done by previous researchers, namely the potential of the Bancakan game in developing the motor skills of students. This was a qualitative with descriptive research method. The subjects in this study were 30 students of the fourth grade of elementary school. The results of the research showed that the three aspects are: (1) speed; (2) eye and hand coordination indicates a good category, while the agility aspects in the category are less. Thus, the researchers concluded that the traditional game of Punching is capable of developing motor skills of fourth-grade students quite well.